1 hug please : re-discovering and embracing ways of affection through illustrated narrative - Lee, Phoebe Wen Ting (Nanyang Technological University, 2020)
Humans are inherently affectionate creatures, be it physical or not. However, as some grow through distant parenting, bustling working cultures, and the insane pace of our capitalistic modern society, they may find themselves chasing after tangible successes in order to enjoy life or simply survive, and eventually have less and less energy to care for themselves emotionally, much less for others. My project uses illustration in a narrative format and satirises our competitive, productivity-driven working landscape; through following an average character of this society who finds themselves stumbling upon the outlawed black market of intimacy, this project aims to explore the simplest of affections through new eyes, prompting readers to rediscover and renew the importance of affection in their lives. It highlights the different ways one can share and embrace intimacy with others, and encourages reflection on our own emotional connections with the people around us as we traverse our hectic lifestyles.